THE AUTHORITY OF THE INDONESIAN NATIONAL POLICE IN HANDLING CRIMES OF FIDUCIARY SECURITY CONTROLLED BY THIRD PARTIES - herawati kusumaningsih (Journal Philosophy of Law, 2020)
This article aims to discuss the authority of the Indonesian National Police in overcoming crimes of fiduciary security controlled by third parties as well as obstacles related to the authority of the Indonesian National Police in overcoming crimes of fiduciary security controlled by third parties. The writing of this article uses a normative juridical approach, which is based on primary and secondary data. Methods of data analysis using qualitative analysis. The research shows that the Authority of the Indonesian National Police in Handling Crimes of Fiduciary Acts controlled by third parties has the authority to maintain public security and order, law enforcement, protection, protection, and community services. They also play a role in providing security assistance implementation of court decisions or execution of fiduciary security. However, in practice, there are obstacles encountered. The obstacles include internal and external constraints also efforts to overcome the authority of the Indonesian National Police in overcoming fiduciary crimes: a. There is still a lack of facilities and infrastructure, as well as an operational budget. b. There are no criminal sanctions against third parties or other parties who control the object of the fiduciary security. c. If a creditor carries out the title of executorial or droit de suit, the debtor often does not fulfill it following Article 30 of Law Number 42 of 1999. Thus the execution process is often cancelled due to rejection from the debtor or mobilizing family or masses. d. Creditors feel aggrieved by incomplete fiduciary collateral as before.